Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 7346 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ambrosia artemisiifolia L.", { "or" : [ "Country is Germany", "Country is Norway", "Country is Serbia", "Country is Russian Federation", "Country is Belgium", "Country is Finland", "Country is Portugal", "Country is Bulgaria", "Country is Denmark", "Country is Lithuania", "Country is Latvia", "Country is France", "Country is Ukraine", "Country is Hungary", "Country is Sweden", "Country is Slovenia", "Country is Moldova, Republic of", "Country is Belarus", "Country is Slovakia", "Country is United Kingdom of Great Britain and Northern Ireland", "Country is Georgia", "Country is Estonia", "Country is Switzerland", "Country is Greece", "Country is Italy", "Country is China", "Country is Spain", "Country is Kazakhstan", "Country is Austria", "Country is Czechia", "Country is Azerbaijan", "Country is Poland", "Country is Romania", "Country is Türkiye", "Country is Bosnia and Herzegovina" ] } ] } The dataset includes 7346 records from 117 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0093178-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences